PRESSING MORTALITY RATE THROUGH SCREENING oral cancer - L. K. Widnyani Wulan Laksmi; I Gede Budhi Setiawan; Sri Maliawan (E-Jurnal Medika Udayana, 2013)
Based on World Health Organization (WHO) data, oral cancer is one of malignancy with the highest mortality. In USA, there are more than 30.000 new cases every year. We can find many risk factors of oral cancer in our daily living. Moreover, it’s easy to find the main risk factors in our society, they are smoking, alcohol consumption, tobacco consumtion, viral infection, and bad oral hygiene. For the early stadium, Five-years survival rate is about 82% and 61% for all stadium. But, more than 50% of oral cancer has been distributed (metastatic) regionally and also into the other organ far away from the oral itself when it’s detected. It will decrease 5-years survival rate to be less than 50%. So that, it’s really important to detect the oral cancer at the earlier stadium. Screening is the way to find the earlier stadium. Screening is done by some methods, start from the anamnesis, physical examination, toluidine blue staining, endoscopy, cytology, telomerase examination, and also PET-scan if it’s possible (because of the financial reasons).